The Impact of Corporate Governance Mechanisms on Corporate Tax Avoidance in Indonesia Public Companies for the Period 2019–2023 - Hananto Pratama, Yosua; Venusita, Lintang (International Economic Conference of Business and Accounting, 2025)
Tax avoidance remains a critical issue in Indonesia. This study analyzes the impact of corporate governance mechanisms on tax avoidance in non-financial public companies in Indonesia during 2019–2023. Data were obtained from annual reports of 171 companies (670 observations) and analyzed using multiple linear regression with a Random Effect Model. Independent variables include audit quality, audit committee size, managerial ownership, independent board of commissioners, and institutional ownership. Results show that audit quality and managerial ownership reduce tax avoidance, while the other three variables have no significant effect. Regulators are advised to strengthen the roles of external auditors and managerial ownership in corporate governance.